Meningkatkan Prestasi Belajar melalui Model Problem Based Learning Pokok Bahasan Sistem Pernapasan Manusia pada Kelas XI MIA 2 SMA Negeri 2 Bungku: Problem based learning dipilih karena memiliki sifat berpusat pada pelajar dan menekankan pada kemandirian belajar. Tujuan penelitian ini adalah mendeskripsikan model problem based learning yang dapat meningkatkan prestasi belajar pelajar dan menganalisis peningkatan pemahaman pelajar pokok bahasan sistem pernapasan manusia setelah diterapkan problem - marhumi, Umi; Kaharudin, La Ode; Rumakefing, Hartina (Universitas Muslim Buton, 2022)
Problem based learning was chosen because it has a learner-centered nature and emphasizes independent learning. The purpose of this study is to describe a problem based learning model that can improve student learning achievement and analyze the increase in student understanding of the subject of the human respiratory system after problem based learning is applied. This research was conducted at SMA Negeri 2 Bungku, students of class XI MIA 2, totaling 30 students for the 2021/2022 academic year, having the address Bente, Bungku Tengah District, Morowali Regency, Central Sulawesi Province. The data analysis technique in this study was using descriptive statistics, namely calculating student learning completeness. The test achievement shows that the Teaching Completeness Criteria (TCC) in the first cycle are 70% or 21 students and 30% or 9 students are incomplete with a total of 30 students. Then in the second cycle of the Teaching Completeness Criteria (TCC) in the second cycle there were 90% or 27 students and only 10% or 3 students who did not complete the total number of students as many as 30 students. Cycle III Teaching Completeness Criteria (TCC)) with a maximum score of: 100% of the total 30 students